FOTOVOLTAİK ETKİ KULLANILARAK FARKLI AÇIK ALANLARDAKİ DİNLENME YERLERİNİN SERİNLETİLMESİNİN ÇEVRESEL VE EKONOMİK FAYDALARININ ARAŞTIRILMASI - TUNA, ÖMER (Fırat Üniveristesi, 2014)
Bu çalışmada, literatürde ilk defa çardak ve balkon bölgesinin (20-24 m2) güneş pili destekli sisleme sistemi ile serinletilmesi Elazığ (38.6775? K, 39.1707? D)'da yapılmıştır. Bu sistem ile çardak ve balkon bölgesinin sıcaklığı düşürülmüş, bağıl nemi ise arttırılmıştır. Güneş pili modülü (fotovoltaik modülü)'nün MATLAB programı ile modellemesi de yapılmıştır. Ayrıca bu çalışmada, kurulan sistemin sık kullanılan klima sistemlerine göre çevresel ve ekonomik yönden avantajları da vurgulanmıştır.

In this study, for the first time encountered in the literature, solar-assisted cooler with misting system established on arbor and balcony with area of 20-24 m2 and georeferenced in Elazig (38.6775? N, 39.1707? E), Turkey is presented. Here, we present a system that reduces interior temperature of the arbor and balcony while increasing humidity. The model of the photovoltaic module was implemented using a MATLAB program. Also in this study, according to the established system commonly used air conditioning system is environmentally and economically are also highlighted.
The investigation of environmental and economical benefits of cooling of different outdoor recreational areas by using photovoltaic effect
Keywords: Enerji